Efficient Recovery of Waste Cotton Fabrics Using Ionic Liquid Methods - Zhang, Xiaozheng; Zhou, Wenhao; Xing, Wenhao; Xu, Yingjun; Zhang, Gangqiang (Polymers, 2025)
Cotton fiber, renewable natural cellulose, make up the largest portion of textile waste. The ionic liquid method has been successfully employed to regenerate waste colored cotton fabric in this study, offering a comprehensive approach to the recycling of waste cotton. The chemical recovery process for reclaimed cellulose materials is crucial for high-value recycling of waste cotton fabrics. In this study, waste and new, colored and white cotton fabrics were used as experimental subjects. The breaking strength, degree of polymerization, iodine adsorption equilibrium value, and crystallinity between old and new fabrics were investigated. Ionic liquid 1-allyl-3-methylimidazole chloride ([AMIM]Cl) and zinc chloride (ZnCl2) were selected to dissolve decolorized waste cotton fabric. Optimal conditions for dissolving the fabric using [AMIM]Cl were investigated. The best dissolution conditions identified were DMSO at a ratio of 1:1 with a dissolution temperature of 110 °C over a duration of 120 min. Additionally, the optimal film formation parameters included a solution concentration of 6%, solidification time of 3 min, and solidification bath temperature of 0 °C. Regenerated cellulose films from both the ionic liquid system (A-film) and zinc chloride system (Z-film) were prepared. The characteristics of the film produced using the most advanced technology were systematically investigated and evaluated. The results of this study provide a crucial theoretical foundation for the recovery and regeneration of waste cotton fabrics.